Observation of intra- and inter-band transitions in the optical response of graphene - Malard, Leandro M. (2013)
The optical conductivity of freely suspended graphene was examined under non-equilibrium conditions using femtosecond pump-probe spectroscopy. We observed a conductivity transient that varied strongly with the electronic temperature, exhibiting a crossover from enhanced to decreased absorbance with increasing pump fluence. The response arises from a combination of bleaching of the inter-band transitions by Pauli blocking and induced absorption from the intra-band transitions of the carriers. The latter dominates at low electronic temperature, but, despite an increase in Drude scattering rate, is overwhelmed by the former at high electronic temperature. The time-evolution of the optical conductivity in all regimes can described in terms of a time-varying electronic temperature.